A new photochromic Gd-MOF with photoswitchable bluish-white to greenish-yellow emission based on electron transfer. Issue 93 (9th November 2020) - Li, Pei-Xin; Xie, Zhi-Xin; Jin, Ai-Ping; Li, Jing; Guo, Guo-Cong
Abstract : A new Gd-MOF exhibits interesting properties of photoswitchable bluish white light to greenish yellow light emission as a result of electron transfer (ET). Photoluminescence studies on the dual-emitter Gd-MOF, which paves the way for white emission though ET. Abstract : Utilization of photochromism in photo-switchable white-light emitters (WLEs) is a challenging task. In an effort to achieve this, we have recently developed a new Gd-MOF using a photoactive pyridinium-based inner salt. The compound shows interesting photoswitchable bluish white light to greenish yellow light emission as a result of electron transfer, a phenomenon that has not been observed previously in photochromic crystal compounds.